Oncolytic virotherapy of glioma: what does it need to make it work?. (November 2011) - Muik, Alexander; von Laer, Dorothee
Oncolytic virotherapy is a highly promising approach, with diverse viruses currently under development as therapeutic agents to treat malignant glioma. Although the first clinical trials did not show toxicity or serious adverse events related to intracerebral administration, overall the antitumor efficacy has fallen short of expectations. This article discusses multiple options on how to improve and maximize the effectiveness of oncolytic virus therapy in brain cancer, including strategies to enhance safety by attenuating neurovirulence via cancer-specific cell-targeting, increasing antitumor potency by transgene-arming and integrating the ability to trigger an effective antitumoral immune response, as well as developing optimized delivery routes in order to boost intratumoral viral distribution. Eventually, it will highlight the use of multipronged approaches, combining multiple modes of action of different agents.